2012
DOI: 10.1074/jbc.m111.277194
|View full text |Cite
|
Sign up to set email alerts
|

CENP-E Kinesin Interacts with SKAP Protein to Orchestrate Accurate Chromosome Segregation in Mitosis

Abstract: Background: CENP-E is a kinetochore-associated kinesin responsible for chromosome congression in mitosis. Results: CENP-E interacts with SKAP to orchestrate kinetochore-microtubule interaction. Conclusion: The SKAP-CENP-E interaction links kinetochore structural components to the spindle microtubule attachment in the centromere. Significance: SKAP cooperates with CENP-E to ensure chromosome stability in cell division.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
64
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 48 publications
(67 citation statements)
references
References 40 publications
3
64
0
Order By: Relevance
“…A recent study speculates that the SKAP⅐Astrin complex localizes and regulates microtubule plus-ends (13). Our investigation of protein networks interacting with CENP-E has led to the identification of SKAP-CENP-E interaction (14). Our study showed that SKAP cooperates with CENP-E to orchestrate kinetochore-microtubule interaction for faithful chromosome segregation (14).…”
mentioning
confidence: 90%
See 2 more Smart Citations
“…A recent study speculates that the SKAP⅐Astrin complex localizes and regulates microtubule plus-ends (13). Our investigation of protein networks interacting with CENP-E has led to the identification of SKAP-CENP-E interaction (14). Our study showed that SKAP cooperates with CENP-E to orchestrate kinetochore-microtubule interaction for faithful chromosome segregation (14).…”
mentioning
confidence: 90%
“…Plasmids and Recombinant Protein Production-The fulllength SKAP mRNA was amplified as described previously (14). GFP-tagged SKAP full-length and deletion truncations were cloned into pEGFP-C2 (Clontech).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Fig. 2D, right panel, lanes [15][16][17][18], Western blotting analyses with a monoclonal antibody of GFP demonstrated that the GFP fusion proteins containing the C-terminal TIP150, in addition to full-length GFP-TIP150, were readily retained on GST-CTN matrix. The N-terminal domain also exhibited weak binding activity toward CTN (Fig.…”
Section: Identification Of a Novel Tip150-ctn Complex In Interphasementioning
confidence: 99%
“…Because TIP150 protein levels remain unchanged during the cell cycle, we sought to examine the role of TIP150 in interphase cells. To study the molecular association of TIP150 with other microtubule end-binding proteins, we carried out an affinity isolation of a TIP150-containing protein complex followed by mass spectrometric identification of tryptic peptides derived from the individually sliced bands as described previously (17,18). As shown in Fig.…”
Section: Identification Of a Novel Tip150-ctn Complex In Interphasementioning
confidence: 99%